2014
DOI: 10.1186/s12879-014-0565-5
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of regimen-modification from first-line antiretroviral therapy in Thailand: a cohort study

Abstract: BackgroundAntiretroviral therapy markedly reduced mortality in HIV-infected individuals. However, in the previous studies, up to 50% of patients are compelled to modify their regimen in middle and low-income countries where salvage drug is still limited. This cohort study aimed to investigate the incidence and predictors of regimen modification from the first-line antiretroviral regimen in northern Thailand.MethodsAll HIV-infected patients starting antiretroviral therapy (ART) with generic drug (GPOvir®; stavu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…The rate of initial regimen change among adult HIV patients on HAART was found to be 10.11/100PY (95 % CI 8.29, 12.6 PY). This finding is lower than a study conducted in Thailand 13.8/100PY [ 8 ], multicenter study in North America and Europe 14.4/100PY [ 7 ], Brazil 28.3/100PY [ 10 ] and Swiss 41.5/100PY [ 9 ]. This might be explained by the difference in defining outcome variables, since in our case we did not considered treatment discontinuation as regimen change unless they restart with different regimen.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The rate of initial regimen change among adult HIV patients on HAART was found to be 10.11/100PY (95 % CI 8.29, 12.6 PY). This finding is lower than a study conducted in Thailand 13.8/100PY [ 8 ], multicenter study in North America and Europe 14.4/100PY [ 7 ], Brazil 28.3/100PY [ 10 ] and Swiss 41.5/100PY [ 9 ]. This might be explained by the difference in defining outcome variables, since in our case we did not considered treatment discontinuation as regimen change unless they restart with different regimen.…”
Section: Discussionmentioning
confidence: 65%
“…A multi-center study in North America and Europe showed that the incidence of regimen change were 14.4/100 person years (PY) [ 7 ]. Furthermore, 13.8/100PY in Thailand [ 8 ], 41.5/100PY in Swiss [ 9 ], 28.3/100PY in Brazil [ 10 ], 16.2/100PY in West Africa [ 11 ], 18.6/100PY in Kenya [ 12 ] and the proportion of regimen change in Ethiopia was 21.8 % [ 13 ]. Different studies revealed that baseline regimen [ 1 , 12 , 14 ], WHO stage [ 12 , 15 ], CD4 count [ 6 , 16 , 17 ] and patient weight [ 12 , 15 ] were some predictors of initial regimen change.…”
Section: Introductionmentioning
confidence: 99%
“…An assessment of the rate of initial regimen changes continuously and its predictor helps to keep patients on the first ART regimen as much as possible. 19 In this study, the incidence rate of initial ART regimen change was 11.36 (95% CI: 9.32, 13.83) per 100 personyears and the median time to initial regimen change was found to be 54 months (95% CI: 47.614, 59.819). The cumulative probability of surviving on the initial regimen at the end of the follow-up period was 52%.…”
Section: Discussionmentioning
confidence: 55%
“…A rate of treatment modi cation was 41.5 per 100 person year from the Swiss HIV Cohort Study 6.3 per 100 person years in a Swaziland Cohort and 13.8/100 person-year in Northern Thailand (7,8,9). Moreover, 20% of patients in Southern India, 83% in Nigeria changed their rst ART regimen (10,11).…”
Section: Introductionmentioning
confidence: 99%